2004
DOI: 10.28945/305
|View full text |Cite
|
Sign up to set email alerts
|

Software for the Synergistic Integration of Science with ICT Education

Abstract: Executive SummaryThe realization of information and communication technology (ICT) literacy is a global and complex objective. It has been argued that it cannot be accomplished by single-focused, stand-alone curricula. Instead, it has been recommended that ICT education be integrated into the instruction of other disciplines to effectively promote technical proficiency, discipline knowledge acquisition, and cognitive development. The Chemistry Is in the News (CIITN) Project exemplifies this integration through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The study results confirmed the strong relation between usage of ICT by the individuals and their scientific literacy (Wu & Glaser, 2004). However, as it turns out the nature of this relation depends on the way of using ICT in learning and the level of skill to use it as well as the nature of learning tasks entrusted to the students (Luu & Freeman, 2011).…”
Section: Teacher Csupporting
confidence: 66%
“…The study results confirmed the strong relation between usage of ICT by the individuals and their scientific literacy (Wu & Glaser, 2004). However, as it turns out the nature of this relation depends on the way of using ICT in learning and the level of skill to use it as well as the nature of learning tasks entrusted to the students (Luu & Freeman, 2011).…”
Section: Teacher Csupporting
confidence: 66%
“…They then further explore the chemistry and social, political and philosophical elements of the topic through questions and answers. The students create portfolios via the CIITN webtool (Glaser, Wu, and Sui 2004;Wu and Glaser 2004) which provides a template for students to construct portfolios on the Internet. The student groups then peer review the portfolios using the webtool, and also going through a constructive review round, revision and final review Glaser and Carson 2005).…”
Section: Chemistry Is In the News In The Classroommentioning
confidence: 99%
“…Following the final round of peer review of the portfolio, students login to the CIITN webtool Wu and Glaser 2004) as an individual and carry out intra-group peer review. Once logged into their individual accounts, the students can access an electronic copy of the rubric.…”
Section: Ciitn Intra-group Peer Reviewmentioning
confidence: 99%
“…Building on a century of general education policy, the National Science Foundation of the United States recommended that science, technology, engineering, and mathematics (STEM) teachers “...model good practices that increase learning; start with the student’s experience, but have high expectations within a supportive climate; and build inquiry, a sense of wonder and the excitement of discovery, plus communication and teamwork, critical thinking, and life-long learning skills into learning experiences.” We developed “Chemistry Is in the News (CIITN)” to teach chemistry in the context of real-world issues and to expose students to some aspects of science communication. In fact, science communication involves all kinds of interactions among STEM professionals and with the public. The central competence in scientific writing is technical communication in the STEM disciplines.…”
Section: Introductionmentioning
confidence: 99%